2022
DOI: 10.3390/foods11070917
|View full text |Cite
|
Sign up to set email alerts
|

Development of Innovative Candied Chestnuts from Three Chestnut Cultivars Grown in Portugal

Abstract: The main purpose of this work is the development of a value-added product (candied chestnuts) from Portuguese chestnut (Castanea sativa) cultivars (Martainha, Longal and Judia), as a way to minimize product loss and wastes. To accomplish this goal, the effects of rehydration, cooking, and syrup conditions on composition, textural properties, and colour parameters of candied chestnuts were investigated. The obtained results revealed that the optimal conditions to prepare candied chestnuts with a sweet taste, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The total chromatic difference (∆E) is calculated using Formula (4). Based on the different degrees of yellow peach color, the ∆E is divided into three levels [ 24 ], 0.0 < ∆E ≤ 2.0 corresponds to Class 0, representing color difference is almost invisible to human vision; 2.0 < ∆E ≤ 3.5 corresponds to Class 1, which means that most people cannot identify color difference and professionally trained people can identify it; 3.5 < ∆E corresponds to Class 2, representing color difference can be distinguished. The ∆E is obtained as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The total chromatic difference (∆E) is calculated using Formula (4). Based on the different degrees of yellow peach color, the ∆E is divided into three levels [ 24 ], 0.0 < ∆E ≤ 2.0 corresponds to Class 0, representing color difference is almost invisible to human vision; 2.0 < ∆E ≤ 3.5 corresponds to Class 1, which means that most people cannot identify color difference and professionally trained people can identify it; 3.5 < ∆E corresponds to Class 2, representing color difference can be distinguished. The ∆E is obtained as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Studies indicate that the CD36 transporter, protein, which is found in taste buds, specifically in the circumvallate and leaf papillae [ 85 ], and the G protein-coupled receptor (GPCR) is the most likely candidate receptors in taste cells, with various taste transduction mechanisms also involved [ 86 ]. Chestnut fruit includes relatively low unsaturated fatty acids (oleic, linoleic, and palmitic acids) [ 8 ]. Studies indicate that roasting chestnuts decreases the concentration of unsaturated and saturated fatty acids.…”
Section: Chestnut Sensory Pleasantnessmentioning
confidence: 99%
“…On the other hand, they may be related to differences in post-harvest, storage, and processing [ 107 ]. In recent years, consumers have preferred healthy, fresh, and high-quality food, and chestnuts have high amounts of healthy bioactive metabolites and nutritional qualities, capable of improving the performance of the human body [ 3 , 8 , 26 ]. Moreover, chestnuts are very versatile when it comes to cooking, they can be present in numerous dishes or consumed alone as a snack.…”
Section: Chestnut In Gastronomymentioning
confidence: 99%
See 2 more Smart Citations